2019
DOI: 10.3390/medicina55090541
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency: Consequence or Cause of Obesity?

Abstract: Obesity is defined as an excess amount of body fat and represents a significant health problem worldwide. High prevalence of vitamin D (VD) deficiency in obese subjects is a well-documented finding, most probably due to volumetric dilution into the greater volumes of fat, serum, liver, and muscle, even though other mechanisms could not completely be excluded, as they may contribute concurrently. Low VD could not yet be excluded as a cause of obesity, due to its still incompletely explored effects through VD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
203
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(227 citation statements)
references
References 50 publications
6
203
1
17
Order By: Relevance
“…Jansen et al reported that BMI should be considered for better estimation of the loading dose of cholecalciferol needed to treat vitamin D deficiency [ 37 ], but they noted that this does not exclude large interindividual variation in dose response. It is well established that obese people have higher risk for vitamin D deficiency [ 38 , 39 ]; Drincic et al reported that most parsimonious explanations for this is simple dilution of 35-OH-vitD in the larger fat and tissue mass [ 40 ]. They also investigated response to graded cholecalciferol supplementation among obese adults [ 41 ], showing that, in obese patients, the dose of vitamin D should be adjusted considering the body size.…”
Section: Discussionmentioning
confidence: 99%
“…Jansen et al reported that BMI should be considered for better estimation of the loading dose of cholecalciferol needed to treat vitamin D deficiency [ 37 ], but they noted that this does not exclude large interindividual variation in dose response. It is well established that obese people have higher risk for vitamin D deficiency [ 38 , 39 ]; Drincic et al reported that most parsimonious explanations for this is simple dilution of 35-OH-vitD in the larger fat and tissue mass [ 40 ]. They also investigated response to graded cholecalciferol supplementation among obese adults [ 41 ], showing that, in obese patients, the dose of vitamin D should be adjusted considering the body size.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not affected by the climatic seasons. Other mechanisms of association between vitamin D and overweight or obesity are widely described in Vranić et al ., according to the consequence and the cause( 21 ). Among them, ‘ its deficiency has been associated with a large number of disorders such as metabolic syndrome, cancers, and autoimmune, psychiatric, and neurodegenerative diseases, but the causative role of VD deficiency in many of these conditions remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ‘ its deficiency has been associated with a large number of disorders such as metabolic syndrome, cancers, and autoimmune, psychiatric, and neurodegenerative diseases, but the causative role of VD deficiency in many of these conditions remains unclear. Since VD deficiency is related to visceral adiposity; it could be used as a biomarker of a visceral adiposity-related dysmetabolic state (cardiovascular diseases, type 2 diabetes, dyslipidemia, arterial hypertension) ’( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, according to the World Health Organization (WHO), over 1.9 billion adults are overweight and among them 650 million are obese [3]. This pathology is strongly related to metabolic disorders such as arterial hypertension, chronic low-grade inflammation, and insulin resistance that could lead to type 2 diabetes [4,5]. Obesity is also strongly linked to ectopic fat accumulation, particularly in the liver, contributing to an emergence of non-alcoholic fatty liver disease (NAFLD) [6].…”
Section: Introductionmentioning
confidence: 99%